Exploration of Student Saturation and Learning Independence Online Learning in Elementary Schools - Desy Nur Wulandary; Riyadi Riyadi; Sri Marmoah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning independently can decrease for students during the Covid-19 pandemic if students experience saturation in learning so that they are lazy to do the tasks given.  This research uses a qualitative approach with a type of case study. The research, placed in Banjar sari Surakarta, used respondents totaling 27 upper-class students from grades 4-6 and 5 interviews with teachers. Data were collected through interviews and direct observation with respondents.  Overall, the level of saturation and independence of students is at an alarming level; this is because students often experience fatigue and boredom, so they are reluctant to do learning and learning tasks independently (such as many students complain of headaches, dizziness, nausea, fatigue, sore eyes, difficulty sleeping, no appetite, tiredness, irritated eyes, lack of rest, and uncomfortable back sitting in front of a smartphone or laptops are too long and the shift from face-to-face to online learning habits cause learners to become bored and confused, thereby reducing their absorption).